(untitled) (Acta Entomologica Serbica, 2020)
In a study of the fauna of phloemo-xylophagous insects on Ulmus minor and their parasitoids and predators in Serbia, new data were obtained on the distribution of the recorded species. Some of these data have been published, but many have not. These unpublished data are presented in this paper, which contains a list of 45 species from two orders, 13 families and 41 genera (16 phloemo-xylophagous species, 24 species of parasitoids and five species of predators). For each of them, data are presented regarding the place and time of their finding.